Mobile Phone Electromagnetic Waves and Pregnancy Outcomes: An Experimental Study in Mice - Armalina, Desy; Susilaningsih , Neni; Sutanto, Heri; Sunarno, Sunarno (Graduate School, Universitas Brawijaya, 2025)
This study investigated the impact of mobile phone–derived electromagnetic wave (EMW) exposure on the uterus and progeny of pregnant Balb/c mice. Fourteen pregnant mice were randomly assigned to two groups (n=7 each). The control group (CG) was not exposed to EMW. In contrast, the experimental group (EG) was subjected to continuous exposure to EMW at a whole-body specific absorption rate (SAR) of 1.74 W.kg-1 for 24 hours daily from gestational day (GD) 1 to 19. On GD 20, all mice were euthanized, and body weight, oxidative stress biomarkers, and uterine histological parameters were assessed. Maternal body weight at termination showed a significant reduction in EG compared with CG (p < 0.05). However, differences in overall body weight gain, malondialdehyde (MDA), and superoxide dismutase (SOD) levels were not statistically significant (p > 0.05). Histological evaluation revealed marked alterations: endometrial scores were significantly higher in EG (3.32) than in CG (0.56) (p < 0.05), and myometrial scores were elevated in EG (1.72) versus CG (0.64). Endometrial thickness was reduced in EG (0.748 mm) compared with CG (1.470 mm) (p < 0.05), whereas myometrial thickness showed no significant difference. Continuous EMW exposure (24 h.day-1, GD1–GD19; SAR 1.74 W.kg-1) was associated with lower maternal weight at GD20, reduced litter size, higher endometrial/myometrial injury scores, and reduced endometrial thickness, while MDA and SOD differences were not statistically significant (p > 0.05). These findings warrant further studies to clarify the mechanisms involved without overstating the changes in oxidative biomarkers.